ANALYSIS OF THE SURFACE PROPERTIES OF ZIZIPHUS JOAZEIRO MART. AND ITS PHYSICAL AND MECHANICAL EFFECTS UNDER PORTLAND CEMENT MORTAR - de Souza Dias, Leonardo; Soares de Oliveira, Cledualdo; Arruda dos Santos, Robson (Journal of Interdisciplinary Debates, 2021)
Surfactants are products widely used in many segments of the industry and because they exhibit many properties they can intensify or improve some properties of the products in which they are used. Natural surfactants are obtained by isolating material of animal or vegetable origin without undergoing chemical changes in its structure. An example of a natural surfactant is that obtained from the Juá husk. Considering the relevance of Juá for obtaining natural surfactants, this work will analyze the effects on physical and mechanical properties that the incorporation, in different proportions, of the powder additive produced from the husk of the trunk of Ziyphus Joazeiro Mart. can offer Portland cement mortar CP-II - Z. The study was carried out at the IFPB - Campus Cajazeiras facilities. Tests were carried out that seek to evaluate the surfactant properties provided by Ziziphus Joazeiro Mart. and its physical and mechanical effects in the mortar. The production of Portland cement mortar combined with the “husk” additive of Ziyphus Joazeiro may be able to result in structures with optimized physical and mechanical characteristics, especially with regard to the consumption of water in the mixture of water, aggregate and binder, in workability and mechanical resistance, consequences resulting from the surfactant properties inherent in the studied composite